TCH-018 Formulation of an Oral Solution Containing "Potion JouliÈ" Phosphorus to Counteract the Shortage of Phosphoneuros. (12th March 2013) - Pailhas, L; Therasse, C; Papon, A; Brion, F; Storme, T
Abstract : Background: In October 2011 a shortage of Phosphoneuros became apparent. This oral solution containing phosphorus is prescribed in the treatment of diseases where phosphorus intake is essential. None of the available drugs was suitable for paediatric needs. Literature searches were conducted to identify formulas in national formularies and pharmacopoeias or already developed in other compounding hospitals, but no consensus 'Potion Joulié' formula was found. Purpose: To provide patients with a concentrated oral solution of phosphorus. A feasibility study was performed. The aim was to give an expiry date of 3 months. Materials and Methods: A batch of 3 bottles was produced. Visual appearance, pH, phosphorus and sodium contents were determined. At M0, M1 and M3 a microbiological assay was performed according to the Ph Eur (5.1.4). Results: The formula we adopted consists of (for 100 ml): 20.40 g of phosphoric acid 50 per cent, 16.5 g of sodium phosphate dibasic anhydrous, 50 mL of sterile water and simple syrup. The phosphorus strength of 67.4 mg/mL is close to that of Phosphoneuro. For 12 weeks, the solution appeared unchanged, clear and colourless. pH about 4.14 remained constant. Sodium and phosphorus contents were stable and the observed values were within 10% of the theoretical values. Microbiological results were in accordance with European Pharmacopeia: viable aerobic bacteria ≤ 10 3 (CFU/ml), fungal ≤ 10 2, no E.coli. Conclusions: Microbiological compliance and physicochemical stability were verified at 12 weeks according to the standards of the European Pharmacopeia. After users had insisted, the French Regulatory agency urged Bouchara Recordati to produce Phosphoneuros again, effective in May 2012. This is an example of the hospital pharmacist's role in compounding drugs to allow patients to continue their treatment in case of shortages of commercial products. No conflict of interest.